Efektivitas Game Edukatif Math Playground dalam Meningkatkan Kemampuan Number Sense Siswa Sekolah Dasar berdasarkan Aspek Sociomathematical Norms - Aurellia, Kirana Reza; Maarif, Samsul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the effectiveness of Math Playground, an educational game in improving students' number sense abilities by considering the aspect of sociomathematical norms. The research method used is a quasi-experiment with a nonequivalent control group design. The research sample was 60 students in grade IV of SDN Kramat Jati 24 which were divided into two classes: one class as an experimental group using the educational game Math Playground, and one class as a control group that did not use the game. Data were collected through number sense tests before and after the intervention, as well as questionnaires on sociomathematical norms. Data analysis was carried out using the N-Gain test, hypothesis test with Independent Sample t Test, and two-track Anova test. The results of the N-Gain test in the experimental class showed an average N-Gain value (%) of 68.3947, while the average N-Gain value (%) in the control class was 42.0701. The results of the t-test showed a significance value of 0.000 < 0.05. The results of the two-track Anova test showed a significance value in the Sociomathematical Norms section of Sig. 0.000 < 0.05, and a significance value in the Class * Sociomathematical Norms section showed a result of Sig. 0.191 > 0.05.